Políticas públicas e qualidade da educação básica: o IDEB como subsídio às ações da gestão pública - Oliveira, Telma de Almeida de (2014)
The present study is thematic access to information about public school is from IDEB as a public policy aimed at improving the quality of basic education. In this sense, as construction of the problem of guiding this research study, it was shown the following question: how can IDEB to subsidize the public manager in the context of improving the quality of basic education? Thus, this study, in general aim to analyze how IDEB - Index of Basic Education Development can subsidize public administration with a view to improving the quality of basic education. Both were established for specific purposes, the following: a) Characterize the IDEB contextualized as an index of public policies for Basic Education b) Characterize the principles of Public Management and its relations with the IDEB. As main justifications of the study are presented as foundations relevance of indices as tools that assist in measuring the quality of teaching. This initiative coming from the rulers as public policy can be taken as a direction for managers of schools aprimorem the process of improvement of services in education, based on the results of the Index of Basic Education Development ( IDEB ) Assessment System Basic Education ( SAEP ), Assessment of Basic Education of Paraná System ( SAEB ), allowing the manager to develop projects and actions to improve the quality of education and hence the improvement in learning from the information you can find out about each student. For schools to provide a quality education requires that the community be involved in public policy , researching information about the schools, in places of education departments data concerning school employees, school meals, expenses, purchases, transfer of government and other information about the school studied , are possible to monitor the day to day school with the information provided. Thus, it is considered popular participation as a fundamental control and aid in defining public policies to be executed in the context of public management for Basic Education.